TRADISI PENYERAHAN PERABOT RUMAH TANGGA DALAM UPACARA PERNIKAHAN DI DESA BAGOR WETAN SUKOMORO NGANJUK PERSPEKTIF ‘URF - Fariqoini, Azimatul; Maryam Qurotul Aini, Siti (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
"Mahar" is something that must be present in a marriage. It is a gift given by a husband to his wife. According to Wahbah al-Zuḥaily, mahar is "property that becomes the right of a wife due to the occurrence of a contract or actual intercourse." In addition to mahar, there are also "srah-srahan" or gifts brought by the groom's family to the bride's family. The form of srah-srahan varies according to the traditions of each region, ranging from food, clothing, to even household items. This article will answer how the tradition of presenting household items in the wedding ceremony in Bagor Wetan Sukomoro Nganjuk Village is practiced and how the "urf" views the tradition of presenting household items in Bagor Wetan Sukomoro Nganjuk Village. This type of research is field research using a qualitative approach. The conclusion of this research is that the tradition of presenting household items in Bagor Wetan Village is a tradition that has existed since ancient times. This tradition is carried out by the groom's family and is done after the wedding ceremony along with the "temu manten" ceremony, where all the household items and other srah-srahan items are brought by the groom's entourage. In terms of material, the tradition of presenting household items is included in "urf amali," in terms of its scope of use, the tradition is included in "urf khas," and in terms of its evaluation of good or bad, the tradition is included in "urf Shahih."